Pleural fluid cytology, biochemistry and adenosine deminase level study in differentiating tubercular and non tubercular causes of pleural effusion - Uddin, Kazi Shihab; Sarker, Md Mahbub Rashid; Razzaque, Md Abdur; Ali, Md Zulfikar (KYAMC Journal, 2018)
Background: Adenosine deaminase (ADA) level in pleural fluid study has gained popularity for quick diagnosis and treatment of tuberculous pleural effusion in tuberculosis burden countries. Studies have confirmed high sensitivity and specificity across the world. Pleural fluid cytology, biochemistry and malignant cell examinations are already in use and widely available. Objectives: Diagnostic approach to quickly differentiate between tubercular and non tubercular pleural effusions by analyzing cytology, biochemistry and ADA level. Materials & Methods: This study was carried out on 85 patients who were admitted or visited outpatient department with pleural effusion. The pleural fluid study was including measurement of ADA level was done. Results: 41 cases were diagnosed as tubercular pleural effusion. Among the low ADA group, 9 cases were diagnosed as malignant pleural effusion with positive malignant cell and 13 cases were transudative effusion.7 cases were diagnosed as parapneumonic effusion with exudative fluid, neutrophilic cell distribution and mixed ADA activity. Conclusion: ADA was found positive with a mean value of 88.3 U/L in tubercular pleural effusions. Non tubercular pleural effusion showed low ADA level. However the cytological and biochemical examination of pleural fluid was also found to be important in differentiating tubercular from non tubercular causes. KYAMC Journal Vol. 9, No.-1, April 2018, Page 28-31